Predictable phenotypic, but not karyotypic, evolution of populations with contrasting initial history - Simões, Pedro (2017)
This study was financed by Portuguese National Funds through FCT - ‘Fundação para a Ciência e Tecnologia’ within the projects PTDC/BIA-BEC/098213/2008, PTDC/BIA-BIC/2165/2012 and cE3c Unit FCT funding UID/BIA/00329/2013. I.F. had a PhD grant (SFRH/BD/60734/2009), P.S. has a Post Doc grant (SFRH/BPD/86186/2012) and S.G.S. has a Post Doc grant (SFRH/BPD/108413/2015) from FCT. M.S. is funded by grant CGL2013-42432-P from the Ministerio de Economía y Competitividad (Spain) and grant 2014 SGR 1346 from Generalitat de Catalunya.